(untitled) (Raparin Journal of Humanities (RJH), 2025)
This research studies the aspects and the effects of statelessness of the Kurds in the poetry of Abdullah Pashew. There are a few nations around the world that suffer from the tragedy of being stateless or in other words nations without an established and recognized state for their own. The Kurds are one of those nations that have suffered from being deprived from having an independent and free state along the history. This state of being stateless effects the individuals in a way either leads them to disappointment and various struggles, or it becomes a source for inspiration and creativity for some other individuals, artists and poets for instance. The Kurdish poet, Abdullah Pashew is one of those who has used the problem of his nation, statelessness of the Kurds, as a source for inspiration, creativity and innovation in his poetry. Pashew, an experienced poet who has gone through exile and being a refugee abroad for years, sees the statelessness as a strong tool for creativity in his poetry especially as a matter for defending national identity and expression of deep feelings and thoughts. This research from a descriptive-analytical perspective deals with two main effects of the statelessness on the individuals. First, it argues the impact of lack of identity on individuals leading the poet to fill the void using art and poetry. Second, it deals with the feelings of exile and refugee ness of the poet that leads to artistic expression and writing poems that in fact it changes the negative feelings into creativity.